Friending someone into submission: Verbal cues for understanding. (July 2018) - Schönefeld, Doris
Abstract : This paper takes a usage-based, Construction Grammar perspective to consider how people interpret linguistic utterances containing novel converted denominal verbs in the pattern NP + V + NP + PP. As a novel expression, such verbs are not (yet) conventional signs, and their meanings must be constructed from prompts in the usage event. Candidates of these are i) their base nouns, ii) the context, that is, the surrounding words and phrases and the situation, and iii) the syntactic arrangement of the material used. A quantitative analysis of usage data suggests that these constructions are part of a speaker's linguistic knowledge and can, hence, be taken as available for the identification of the general scene the novel verb will name. The data also reveal strong associations between verbs and prepositions.